Green tea consumption rapidly enhances cognitive performance and flow state during mental tasks in healthy young adults - Chie Kurosaka; Shinji Miyake; Makoto Kobayashi; Chika Tagata; Yuka Tatsumi (PLoS ONE, 2025)
This study examined green tea’s effects on task performance, mental fatigue, workload, and flow experience. Twenty-two healthy young male participants (mean ± SD age = 21.86 ± 1.96 years, range = 18–26 years) completed two 5-min mental tasks (arithmetic and sequential digit search) under three beverage consumption conditions: no beverage (NONE), WATER, and TEA (green tea). In the WATER and TEA conditions, participants consumed 70 mL of beverage three times during the session (total: 210 mL). Subjective Fatigue Feelings was assessed before and after each condition, and subjective evaluations including NASA Task Load Index, Flow Experience Checklist, and Duration Judgment Ratio, were conducted after each task. Results showed no significant differences in task performance across conditions (p > 0.05, η² = 0.11 and η² = 0.02 for MATH and SDS tasks, respectively), likely due to ceiling effects (accuracy > 95%). In the TEA condition, arousal levels were maintained and no increase in mental fatigue was observed, unlike the other conditions. The flow state score in the TEA condition was significantly higher than that in other conditions (NONE vs TEA: p = 0.0009), and participants perceived shorter task duration (NONE vs TEA: p = 0.0016, WATER vs TEA: p = 0.0061). These effects were observed even with small amounts of beverage and short consumption periods, suggesting that habitual intake of low-dose green tea may enhance task engagement and flow experience in everyday tasks.